Case report: Neuronal intranuclear inclusion disease initially mimicking reversible cerebral vasoconstriction syndrome: serial neuroimaging findings during an 11-year follow-up - Lee, Gha-Hyun; Jung, Eugene; Jung, Na-Yeon; Mizuguchi, Takeshi; Matsumoto, Naomichi; Kim, Eun-Joo (Frontiers in Neurology, 2024)
Neuronal intranuclear inclusion disease (NIID) is a rare, progressive neurodegenerative disorder known for its diverse clinical manifestations. Although episodic neurogenic events can be associated with NIID, no reported cases have demonstrated concurrent clinical features or MRI findings resembling reversible cerebral vasoconstriction syndrome (RCVS). Here, we present the inaugural case of an adult-onset NIID patient who initially displayed symptoms reminiscent of RCVS. The 59-year-old male patient’s initial presentation included a thunderclap headache, right visual field deficit, and confusion. Although his brain MRI appeared normal, MR angiography unveiled left posterior cerebral artery occlusion, subsequently followed by recanalization, culminating in an RCVS diagnosis. Over an 11-year period, the patient encountered 10 additional episodes, each escalating in duration and intensity, accompanied by seizures. Simultaneously, cognitive impairment progressed. Genetic testing for NIID revealed an abnormal expansion of GGC repeats in NOTCH2NLC, with a count of 115 (normal range, <60), and this patient was diagnosed with NIID. Our report highlights that NIID can clinically and radiologically mimic RCVS. Therefore, in the differential diagnosis of RCVS, particularly in cases with atypical features or recurrent episodes, consideration of NIID is warranted. Additionally, the longitudinal neuroimaging findings provided the course of NIID over an 11-year follow-up period.